2008
DOI: 10.1007/s12237-008-9107-y
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use Patterns of Newly Settled Southern Flounder, Paralichthys lethostigma, in Aransas–Copano Bay, Texas

Abstract: Southern flounder Paralichthys lethostigma populations have been declining in Texas during the past 25 years. Despite their economic importance, little is known about their juvenile habitat requirements. We examined habitat use patterns of newly settled southern flounder in three zones at varying distances from the Aransas Pass inlet in Aransas-Copano Bay by measuring densities using a beam trawl in replicate estuarine habitat types in each zone. Highest abundance occurred near the inlet in vegetated sandy are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…Aggregated spatial distributions related species communities to different habitat characteristics, emphasizing the importance of maintaining a variety of habitat characteristics and distribution in restored areas (Rashleigh et al, 2009). Nanez-James, Stunz, andHolt (2009) and Ross et al (2009) stress the importance of maintaining vegetated, sandy, shallow habitats in the nearshore of barrier islands as compared to unvegetated, muddy bottoms for maintaining populations of southern flounder in Texas and gulf sturgeon in Louisiana, Mississippi, and Alabama. Nordstrom (2000) and Finkl and Walker (2002) emphasize the importance of maintaining beach profile elevation in nourishment projects, many of which employ the use of dredge material.…”
Section: Dredgingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregated spatial distributions related species communities to different habitat characteristics, emphasizing the importance of maintaining a variety of habitat characteristics and distribution in restored areas (Rashleigh et al, 2009). Nanez-James, Stunz, andHolt (2009) and Ross et al (2009) stress the importance of maintaining vegetated, sandy, shallow habitats in the nearshore of barrier islands as compared to unvegetated, muddy bottoms for maintaining populations of southern flounder in Texas and gulf sturgeon in Louisiana, Mississippi, and Alabama. Nordstrom (2000) and Finkl and Walker (2002) emphasize the importance of maintaining beach profile elevation in nourishment projects, many of which employ the use of dredge material.…”
Section: Dredgingmentioning
confidence: 99%
“…Wells et al (2009) documented the use of inshore mud, shell bank, and offshore mud habitats by a variety of fish species on a drowned barrier island along the Texas shelf. Equally important to creating productive nekton habitat is the maintenance of sandy bottom inlets between barrier islands and other shoreline features (Nanez-James, Stunz, and Holt, 2009;Ross et al, 2009). …”
Section: Dredgingmentioning
confidence: 99%
“…The bag seines used in this study were designed to sample juvenile estuarine fish populations (Martinez-Andrade et al, 2009). While formal gear selection studies were not performed, previous studies on this species have shown this to be an effective gear for sampling juvenile southern flounder (Nañez-James et al, 2009 seine) longitude and latitude coordinates were recorded, and total length (TL) of each fish was measured.…”
Section: Field Collectionmentioning
confidence: 99%
“…The residuals were fitted using a varIdent variance structure from the "nlme" library in R, where each month was allowed to have a different variance (Zuur et al, 2007). All months were tested for significance against January, due to January being shown as the first month of recruitment in Texas (King, 1971;Stokes, 1977;Nañez-James et al, 2009). Nonparametric bootstrapping with replacement (n = 1000) of the resulting coefficients were used to estimate confidence intervals of the gls model parameters without making assumptions about the population distribution.…”
Section: Time Series Analysesmentioning
confidence: 99%
“…Southern flounder spawn offshore at depths of 20 to 60 m during winter months (Stokes, 1977). Currents transport the larvae to shallow water estuaries where they settle out at approximately 8 to 12 mm TL and begin life on the bottom (Glass et al, 2008;Nañez-James et al, 2009;Wenner and Archambault, 2005). Histological analysis shows that gonadal tissue differentiation begins at~75 mm TL at approximately 4 to 6 months of age in North Carolina (Luckenbach et al, 2003).…”
Section: Introductionmentioning
confidence: 99%